Pemanfaatan Media dan Karakteristik Pembelajaran IPAS: Studi Kualitatif Di Kelas Empat Madrasah Ibtidaiyah - Hana, Rissiril; Kholifah, Siti; Ardiyansyah, Moch. Yusuf; Agustin, Nurhaningtyas (Tarunateach: Journal of Elementary School, 2025)
This study analyzes the Characteristics and Media of Science Learning in Grade 4 of MI Al-Hidayah. This study uses a qualitative research type using observation and interview methods. The study results indicate that in MI Al-Hidayah Gesikharjo in science learning in fourth grade, the learning characteristics applied are contextual and the learning media often used are Pictures, Spinner, and LKS. From this study, it can be concluded that the characteristics of science learning in MI AL-Hidayah are contextual and interactive, while the learning media used are pictures/posters, Spinners, and students’ worksheets.